Occupational exposure to platinum drugs during intraperitoneal chemotherapy. Biomonitoring and surface contamination. (1st December 2018) - Ndaw, S.; Hanser, O.; Kenepekian, V.; Vidal, M.; Melczer, M.; Remy, A.; Robert, A.; Bakrin, N.
Highlights: Exposure of the surgical team during intraperitoneal chemotherapy was investigated. Low urinary platinum levels from the surgical team were reported. Urinary levels did not differ significantly between exposed workers and controls. Significant platinum contaminations were observed on the operating room's surfaces. Safety guidelines must be strictly observed. Abstract: Background: Hyperthermic intraperitoneal chemotherapy (HIPEC) has been introduced over the last decade for the treatment of peritoneal carcinomatosis. In this procedure, heated cytotoxic drugs are administered directly into the abdominal cavity, ensuring cancer cells to be exposed while reducing systemic toxicity. More recently, pressurized intraperitoneal aerosol chemotherapy (PIPAC), where the chemotherapeutic drug is injected into the peritoneal cavity as an aerosol under pressure, has been proposed to patients in palliative situation, as a new approach. The amount of drug used is up to 10 fold lower than in HIPEC. The use of cytotoxic drugs poses an occupational risk for the operating room personnel. This study investigated the potential exposure of the medical staff by biomonitoring and surface contamination measurements, during a HIPEC procedure and a PIPAC procedure. Method: Wipe samples were collected from various locations in operating rooms including gloves, hands, devices and floor. Urines samples were collected from 10 volunteers of the medical staff and from a control group. The platinum analysis was performed by inductively coupled plasma mass spectrometry. Results: Significant contaminations were observed on the floor, gloves, shoes and devices. However, urinary platinum was below the limit of quantification (<10 ng/L) for more than 50% of samples from the healthcare workers performing HIPEC and PIPAC. Concentrations did not differ significantly from those reported for the control group. Conclusion: There appears to be little risk of exposure to platinum drugs during HIPEC and PIPAC providing the adequate safety measures are implemented.